Membranforschung für die Öffentlichkeit: Ein Kooperationsprojekt zwischen Fachdidaktik und Fachwissenschaft. Issue 4 (5th September 2017) - von Hoff, Elena; Milsch, Nele; Ehlers, Marc; Waitz, Thomas; Mey, Ingo
Translation abstract: Within this contribution we present a collaborative project between didactic and scientific groups focusing on the development of various science outreach activities concerning the research of the Collaborative Research Center 803. Through this close cooperation research questions and topics on membrane research will be linked to contexts as well as questions relating to our daily lives; hence a number of materials such as experiments, exhibition pieces, videos and adapted primary literature for the formal and non‐formal education sector will be developed. These will be continuously improved in a cyclic process of design, implementation, evaluation and optimization. Placing the focus on the three target groups of students, teachers and the interested public will promote a sustainable communication between science and society.